Dampak Penggunaan Gadget dan Minat Belajar Terhadap Hasil Belajar Siswa SMP Al-Azhar Kota Bekasi - Yosse Amanda Pratama; Valisa Nur Ajizah; Uswatun Hasanah; Muhammad Nur Ikhsan; Rafika Rahmawati (Universitas Palan, 2023)
Gadgets are electronic devices that are used as information media, learning media, and as entertainment. Another benefit of the gadget is that it can connect to the internet and students are familiar with the functions of the internet. This has resulted in many students misusing the use of the internet for negative things, so students must always be under the supervision of their parents. The purpose of this study was to analyze the effect of gadget use and interest in learning on junior high school students' learning outcomes. The type of research used in this research is quantitative research with a correlational descriptive approach, the nature of the data is ex post facto, namely a research conducted to investigate events that have occurred and then look back at past events to find out the factors that could have caused these events to occur. . The technique used by researchers in this study was to use a questionnaire to obtain data on the impact of using gadgets and learning interest on learning outcomes. This research was carried out with 20 students as research subjects and assisted by listening to teachers at Al-Azhar Middle School, Bekasi City. The results showed that the use of gadgets did not significantly influence student learning outcomes. There is a significant influence of the use of gadgets and learning interest on learning outcomes. This can be proven by the strong value of Sig = 0.000 and F count = 12.788 F table = 3.591. So this can be said to be the value and F count > F table and Sig 0.000 > 0 ,05. Based on these results, it can be concluded that the impact of using gadgets and learning interest on learning outcomes has a significant effect on Student Learning Outcomes at SMP AL-Azhar Bekasi City.